Can Policy Be Risk‐Based? The Cultural Theory of Risk and the Case of Livestock Disease Containment. Issue 4 (3rd December 2014) - Duckett, Dominic; Wynne, Brian; Christley, Rob M.; Heathwaite, A. Louise; Mort, Maggie; Austin, Zoe; Wastling, Jonathan M.; Latham, Sophia M.; Alcock, Ruth; Haygarth, Philip
Abstract This article explores the nature of calls for risk‐based policy present in expert discourse from a cultural theory perspective. Semi‐structured interviews with professionals engaged in the research and management of livestock disease control provide the data for a reading proposing that the real basis of policy relating to socio‐technical hazards is deeply political and cannot be purified through 'escape routes' to objectivity. Scientists and risk managers are shown calling, on the one hand, for risk‐based policy approaches while on the other acknowledging a range of policy drivers outside the scope of conventional quantitative risk analysis including group interests, eventualities such as outbreaks, historical antecedents, emergent scientific advances and other contingencies. Calls for risk‐based policy are presented, following cultural theory, as ideals connected to a reductionist epistemology and serving particular professional interests over others rather than as realistic proposals for a paradigm shift.